(untitled) (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
The availability of a reliable campus Wi-Fi network is a key requirement in supporting digital-based academic activities. However, an increase in the number of users during peak hours often causes a decline in network service quality. This study aims to analyze the quality of service (QoS) of the campus Wi-Fi network during peak user hours by referring to the parameters of throughput, delay, jitter, and packet loss. The research method was conducted through direct measurements at several strategic locations on campus, namely lecture buildings, libraries, computer laboratories, and public hotspot areas, during normal hours and peak hours. The measurement results were analyzed descriptively and evaluated based on TIPHON standards. The results showed a significant decrease in throughput during peak hours, especially in areas with high user density. Meanwhile, the delay, jitter, and packet loss parameters increased, but most were still within the TIPHON standard tolerance limits. These findings indicate that although the campus Wi-Fi network can still operate during peak hours, the quality of service provided is not yet optimal. This study is expected to serve as a reference for campus network managers in evaluating and optimizing Wi-Fi infrastructure to improve network service quality on an ongoing basis.